Separation of cyclotron-produced 44Sc from a natural calcium target using a dipentyl pentylphosphonate functionalized extraction resin. (January 2015) - Valdovinos, H.F.; Hernandez, R.; Barnhart, T.E.; Graves, S.; Cai, W.; Nickles, R.J.
Abstract: Significant interest in 44 Sc as a radioactive synthon to label small molecules for positron emission tomography (PET) imaging has been recently observed. Despite the efforts of several research groups, the ideal 44 Sc production and separation method remains elusive. Herein, we propose a novel separation method to obtain 44 Sc from the proton irradiation of calcium targets based on extraction chromatography, which promises to greatly simplify current production methodologies. Using the commercially available Uranium and Tetravalent Actinides (UTEVA) extraction resin we were able to rapidly (<20 min) recover >80% of the activity generated at end of bombardment (EoB) in small 1 M HCl fractions (400 μL). The chemical purity of the 44 Sc eluates was evaluated through chelation with DOTA and DTPA, and by trace metal analysis using microwave induced plasma atomic emission spectrometry. The distribution coefficients ( K d ) of Sc(III) and Ca(II) in UTEVA were determined in HCl medium in a range of concentrations from zero to 12.1 M. The 44 Sc obtained with our method proved to be suitable for the direct labeling of small biomolecules for PET imaging, with excellent specific activities and radiochemical purity. Highlights: Cyclotron-produced 44 Sc is loaded into 50 mg of UTEVA resin after dissolution of 300 mg of nat Ca target in concentrated HCl. 80±4% of the activity at end of bombardment (EoB) is eluted using 400 μL of deionized water in <20 min after EoB. The separation factor of the bulk calcium is 1.2×10 4 . 44 Sc has reactivities or effective specific activities with DOTA and DTPA of 18.1±6.7 and 49±37 GBq/μmol, respectively. Metal impurities in the isolated 44 Sc are: Ca (2.1 mM), Fe (93 μM), Zn (72 μM), Ni (29 μM), Al (6.4 μM) and Mn (2.0 μM).